PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE PADA MATERI PERUBAHAN WUJUD BENDA KELAS IV - Benedikta Sari Lehot; Tasi’awati Salsa Kaliwanovia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning in elementary schools still faces challenges regarding low student engagement due to a lack of variety in instructional methods. This issue impacts conceptual understanding, particularly on the topic of changes in the states of matter. This study aims to determine the effectiveness of implementing the Think Pair Share (TPS) learning model in enhancing the engagement and learning outcomes of IV elementary school students. The methodology employed is descriptive research with a qualitative approach. The subjects of this study involved fourth-grade students. Data collection techniques included observation, interviews, and documentation. The results indicate that the application of the Think Pair Share model successfully increased students' active participation in the learning process, fostered critical thinking skills, and assisted students in better understanding the concept of changes in the states of matter. Furthermore, student interactions and the learning atmosphere became more conducive. Based on these findings, it can be concluded that the Think Pair Share learning model is effective for teaching Science, specifically regarding changes in the states of matter, in IV elementary school classrooms.